EFEKTIVITAS STERILISASI DAN EFISIENSI MEDIA MORASHIGE SKOOG TERHADAP PERTUMBUHAN EKSPLAN LIDAH BUAYA - Maria Theresia Darini (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2012)
The study aims to know the efectivity of sterilization and the efficiency of Morashige Skoog media on the growth of Aloe vera L. explant, has been done in tissue culture laboratory, Faculty of Agriculture Sarjanawiyata Tamansiswa University. The experiment is factorial 4 x 3, arranged in a Completely Randomized Design with three replication. The first factor was sterilization methode (S) consist of four levels, those are: sterilization methode 1 (S 1), methode 2 (S2), methode 3 (S3), and methode 4 (S4). The second factor was concentration of MS media consist of three levels those are : full media (M1), ½ media (M2), and ¼ media (M3). The variables observed were : date of shoot emerge, number and height of shoots, number of leaves and roots, root length, shoot and root fresh weight, shoot – root dry weight and viability potensial of the explant. The result of analysis uses analysis of varians on the significant level 5%, and continued with Duncan’s Multiple Range Test significant level 5%. The conclution of experiment are interaction between sterilization 3, 4 methode, and full and ½ media concentration on viability of explant variable observed. The better of explant growth was gained the efectivity on alcohol of 96% and hyphocloric of 50% as long as 3 minutes sterilization methode, likewise the better of explant growth was gained the efficiency on ½ consentration MS media treatment.